Governance in an emerging suburban world - Hamel, Pierre; Keil, Roger (Pontifícia Universidade Católica de São Paulo, 2016)
Cities are increasingly defined through their peripheries. This observation is the result of what has been explored by urban researchers worldwide. Suburban development, with diverse modalities of governance – through the state, capital accumulation and private authoritarianism – is transforming city regions in an unexpected way. The diversity of spatial forms shaping urban/suburban development is part of a peripheral growth bringing in a new scale for understanding urban issues, the metropolis or the city region. The paper is subdivided in four parts. First, we take into account the expansion of suburban spaces in order to highlight the new urban issues emerging at a city regional scale. Second, we look at framing the mechanisms of suburban governance. Then, after paying attention to the Canadian situation, we compare the model of suburban governance in Anglo Saxon settler societies to other forms and/or models of suburbanization prevailing in other parts of the world.